The extent of social studies teachers’ familiarity with the values of integrity from the point of view of educational supervisors in Kingdom of Saudi Arabia - Almutlaq, Bandar Abdullah Mutlaq; Alshehri, Wafa Abdullah Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the extent of social studies teachers’ familiarity with the values of integrity from the point of view of educational supervisors in Kingdom of Saudi Arabia. This study used the descriptive approach to achieve its goal, and the study tool was built, which was represented by a questionnaire tool, where the study population and sample consisted of all Male and female supervisors of social studies in Riyadh education for this year 1444 AH. The results of the study concluded that there is a high degree of familiarity among male and female social studies teachers with the targeted values of integrity (honesty, honesty, transparency, preservation of property, citizenship) from the point of view of educational supervisors, which was to a great extent. In light of the results, it was concluded The study reached many recommendations, including the importance of integration between the family, school, and society in enhancing the value of integrity for students, the role of school activity in promoting the values of integrity through programs provided by the activity departments, and cooperation with other parties to enhance the values of integrity for students. Holding training programs for male and female social studies teachers to learn about strategies for enhancing the values of integrity among students.